Matching Optimized of Clearance of Bearing Inner and Outer Ring - Chen Guojin; Jin Duting; Chen Chang; Su Shaohui; Li Long (Jixie chuandong)
For the random of deviation step matching algorithm of single inner and outer ring in the fitting procedure certain of,a new iterative algorithm is quoted. The 10 pairs inner and outer rings is chosen after step matching to second matching,the mathematical model of second matching is established and the directed test matrix is introduced to establish the solving model of a new iterative algorithm. Comparing with before second matching,the result shows that randomness of matching is reduced and the y value of bearing increase by 4. 58%.